Almost Î±-Î³-Irresolute Functions - O. Ravi (Journal of New Results in Science)
functions called almost γ-irresolute functions and almost α-γirresolute functions in topological spaces. We obtain several characterizations of these classes and study their properties and investigate the relationships with the known non-continuous functions